Mapping the network biology of metabolic response to stress in posttraumatic stress disorder and obesity - Chacko, Thomas P.; Toole, J. Tory; Richman, Spencer; Spink, Garry L.; Reinhard, Matthew J.; Brewster, Ryan C.; Costanzo, Michelle E.; Broderick, Gordon (Frontiers in Psychology, 2022)
The co-occurrence of stress-induced PTSD and obesity is common, particularly among military personnel but the link between these conditions is unclear. Individuals with comorbid PTSD and obesity manifest other physical and psychological problems, which significantly diminish their quality of life. Current understanding of the pathways connecting stress to PTSD and obesity is focused largely on behavioral mediators alone with little consideration of the biological regulatory mechanisms that underlie their co-occurrence. In this work we use natural language processing (NLP) to extract documented regulatory interactions involved in the metabolic response to stress and its impact on obesity and PTSD from over 8 million peer-reviewed papers. The resulting network describes the propagation of stress to PTSD and obesity through 34 metabolic mediators using 302 documented regulatory interactions supported by over 10,000 citations. Stress jointly affected both conditions through 21 distinct pathways involving only 2 intermediate metabolic mediators out of a total of 76 available paths through this network, Moreover, oxytocin (OXT), Neuropeptide-Y (NPY), and cortisol supported an almost direct propagation of stress to PTSD and obesity with different net effects. Although stress upregulated both NPY and cortisol, the former was found to attenuate PTSD severity, while exacerbating obesity. Likewise, while cortisol had an attenuating effect on PTSD, it exacerbated obesity. The stress-mediated release of oxytocin however was found to concurrently downregulate the severity of both conditions. These findings highlight how a network-informed approach may be highly effective in identifying key mediators like OXT in the treatment of complex stress-mediated co-morbidities.